Transnational radicalism and the connected lives of Tom Mann and Robert Samuel Ross - Kirk, Neville, 1947- (Studies in labour history (Liverpool University Press) ;, 2017)
A pioneering study of the neglected transnational activities and influences of two important, connected socialists, British-born Tom Mann (1856-1941) and Australian-born Robert Samuel 'Bob' Ross (1873-1931).